Transit-Amplifying Cells in the Fast Lane from Stem Cells towards Differentiation - Emma Rangel-Huerta; Ernesto Maldonado (Hindawi Limited, 2017)
Stem cells have a high potential to impact regenerative medicine. However, stem cells in adult tissues often proliferate at very slow rates. During development, stem cells may change first to a pluripotent and highly proliferative state, known as transit-amplifying cells. Recent advances in the identification and isolation of these undifferentiated and fast-dividing cells could bring new alternatives for cell-based transplants. The skin epidermis has been the target of necessary research about transit-amplifying cells; this work has mainly been performed in mammalian cells, but further work is being pursued in other vertebrate models, such as zebrafish. In this review, we present some insights about the molecular repertoire regulating the transition from stem cells to transit-amplifying cells or playing a role in the transitioning to fully differentiated cells, including gene expression profiles, cell cycle regulation, and cellular asymmetrical events. We also discuss the potential use of this knowledge in effective progenitor cell-based transplants in the treatment of skin injuries and chronic disease.